Towards general theories of software engineering - Johnson, Pontus; Ekstedt, Mathias; Goedicke, Michael; Jacobson, Ivar (Science of computer programming, 2015)
The special issue of Science of Computer Programming focuses on the theme of general theories of software engineering. A general theory aims at answering the big questions in its field. Ideally, it should be able to explain and predict important phenomena in the field. A general theory of electromagnetism should help readers to understand why one transformer design is superior to another. Software engineering may be considered by pondering the big questions that general theories of software engineering would address. The software engineering discipline also features a multitude of well-known specific theories in addition to personal general theories.